RNA‐Binding Protein Hnrnpa1 Triggers Daughter Cardiomyocyte Formation by Promoting Cardiomyocyte Dedifferentiation and Cell Cycle Activity in a Post‐Transcriptional Manner - Chuling Li; Yijin Chen; Qiqi Chen; Haoxiang Huang; Michael Hesse; Yilin Zhou; Ming Jin; Yu Liu; Yifei Ruan; Xiang He; Guoquan Wei; Hao Zheng; et al. (Advanced Science)
Abstract Stimulating cardiomyocyte (CM) dedifferentiation and cell cycle activity (DACCA) is essential for triggering daughter CM formation. In addition to transcriptional processes, RNA‐binding proteins (RBPs) are emerging as crucial post‐transcriptional players in regulating CM DACCA. However, whether post‐transcriptional regulation of CM DACCA by RBPs could effectively trigger daughter CM formation remains unknown. By performing integrated bioinformatic analysis of snRNA‐seq data from neonatal and adult hearts, this study identified Hnrnpa1 as a potential RBP regulating CM DACCA. Hnrnpa1 expression decreased significantly during postnatal heart development. With the use of α‐MHC‐H2B‐mCh/CAG‐eGFP‐anillin transgenic mice, Hnrnpa1 overexpression promoted CM DACCA, thereby triggering daughter CM formation and enhancing cardiac repair after myocardial infarction (MI). In contrast, CRISPR/Cas9 technology is used to generate CM‐specific Hnrnpa1 knockout mice. Hnrnpa1 knockout inhibited cardiac regeneration and worsened cardiac function in the neonatal MI model. Nanopore RNA sequencing, RIP assay, IP‐MS, MeRIP‐qPCR, PAR‐CLIP and luciferase reporter experiments showed that Hnrnpa1 induced Mettl3 post‐transcriptional splicing to inhibit m6A‐dependent Pbx1 and E2F1 degradation, thereby increasing Runx1, Ccne1, Cdk2 and Ccnb2 expression to promote CM DACCA. In conclusion, Hnrnpa1 triggered daughter CM formation by promoting CM DACCA in a post‐transcriptional manner, indicating that Hnrnpa1 might serve as a promising target in cardiac repair post‐MI.